Hybrid fibre reinforced polymer and seawater sea sand concrete structures: A systematic review on short-term and long-term structural performance. (27th September 2021) - Bazli, Milad; Heitzmann, Michael; Hernandez, Byron Villacorta
Highlights: Recent studies on hybrid FRP-SWSSC structures were reviewed. Both short-term and long-term performance were presented. Different types of FRP reinforcement for SWSSC structures were covered. Research gaps and recommendations for future works were introduced. Abstract: The use of hybrid seawater sea sand concrete (SWSSC) and fibre reinforced polymer (FRP) composites and, as alternatives for ordinary concrete and conventional carbon steel reinforcement, in coastal areas has attracted researchers' attention. The present paper systematically reviews more than 100 experimental and numerical studies focused on environmental aspects and structural performance of hybrid FRP-SWSSC concrete structures. Besides introducing the ecological benefits of using such advanced and environmentally friendly materials, short and long-term structural performance of FRP-SWSSC structures under different loading configuration and environmental conditions are discussed. Structural performance of different systems, including FRP reinforced SWSSC beams, SWSSC filled FRP tubes, FRP strengthened/wrapped SWSSC members, and glass FRP (GFRP) profiles-SWSSC composite members are presented and discussed. In addition, microstructural properties of materials under different environmental conditions are introduced. Eventually, recommendations for prospect investigations are made. A foundation is provided with this overview which will enable a better understanding of the mechanical and microstructural properties of FRP-SWSSC structures. This overview can also be used to develop design guides for material systems in aggressive environments, particularly in coastal areas.